2D Materials Nanoelectronics: New Concepts, Fabrication, Characterization From Microwaves up to Optical Spectrum. Issue 8 (11th April 2019) - Dragoman, Mircea; Dinescu, Adrian; Dragoman, Daniela
Abstract : The paper presents the state‐of‐the art of nanoelectronic devices based on 2D materials related to the cutting edge of Moore's law. Ballistic electron devices, ferroelectric, and atomically thin heterostructures are analyzed to show the benefits of 2D materials applications in nanoelectronics. It is shown that these new devices fulfill the basic requirements for further developments of new materials and circuits architectures envisaged beyond the Moore law. However, in many aspects, these new devices, concepts, as well as their implementations, are at the very beginning, so that the main obstacles to be overcome and the inherent difficulties to design and fabricate nanoelectronic devices based on single‐atom‐ or few‐atoms‐thick materials are also presented. Abstract : The authors present the state‐of‐the art of nanoelectronic devices based on 2D materials related to the cutting edge of Moore's law. Ballistic electron devices, ferroelectric, and atomically thin heterostructures are studied to demonstrate the benefits of 2D materials applications in nanoelectronics as well. The way ahead the maturity of these devices to enhance Moore's law is analyzed.